Extraction of maximum power from solar with BLDC motor driven electric vehicles based HHO algorithm - Krishna konijeti, Mali Satya Naga; Bharathi, M.L. (Advances in engineering software (1992), 2022)
•Harris Hawks Optimization (HHO) is used to offer a Maximum Power Point Tracking Technique (MPPT) for Photovoltaic (PV) Powered e-Vehicles.•The proposed design would take fewer iterations to reach prime conditions, enhancing the proposed system's overall efficiency.•PID (Proportional Integral Derivative) (e-vehicle) controlled the BLDC engine's speed.•This paper also goes into the modelling of a novel MPPT that is utilized for PV-driven BLDC-based e-vehicles.•A comparison of MPPT results has been shown to demonstrate the superiority of the suggested method in this system. Electric car motors and power electronics have gotten a plenty of concerns recently, because to their rapid growth. DC and 3ϕ induction motors are two of the greatest well-studied electric vehicle (EV) motors. Developing countries, particularly with Brushless DC (BLDC) Motors, have developed their own solutions for EV (BLDC). Controlling the steady-state response and transient, settling time, overshoot, rise time, and other aspects of the 3ϕ BLDC motor is a difficult task. A break in control can make the system unstable and reduce the component's lifespan. Harris Hawks Optimization (HHO) is used to offer a Maximum Power Point Tracking Technique (MPPT) for Photovoltaic (PV) Powered e-Vehicles. By using an HHO technique, the proposed system addresses the issues with traditional MPPT methods. As a result, the design would take fewer iterations to reach prime conditions, enhancing the proposed system's overall efficiency. The BLDC engine's speed is controlled using PID (Proportional Integral Derivative) (e-vehicle). The HHO-based MPPT technique outperformed the others in terms of performance. This paper also goes into the modeling of a novel MPPT that is utilized for PV-driven BLDC-based e-vehicles. Many factors, such as shade, uneven sunshine, and weather conditions, have a role in poor efficiency in real-world situations, demonstrating PV's non-linear features. The MPPT approach mentioned in this article can be utilized to boost overall productivity and lower operating costs for e-vehicles based on the PV framework.